É possível o desenvolvimento de knowledge-intensive business services (KIBS) em regiões periféricas? : o caso dos serviços de engenharia de projetos e da tecnologia da informação no Espírito Santo - Hoffman, Alexsandro Mairink (2009)
The current information technologies and communications technical-economic paradigm (TEP-ICT´S) has opened many opportunities which have been widely used by knowledge-intensive business services (KIBS). This paper aims at discussing KIBS development in peripheral regions. Therefore, it will not only present the theoretical approach which involves KIBS including its 4 distinctive dimensions but also the formation and dynamics of service rendering segments and KIBS activities in Brazil and Espírito Santo, offering a case study on project engineering and information technology companies which took part in a suppliers development program. The major line of reasoning is to propose KIBS has a 5th-distinctive dimension (the institutional dimension) and its importance in peripheral regions. Particularly in Espírito Santo case, said 5th dimension focuses on collaborator qualification institutions.